(untitled) (Analysis in Theory and Applications, 2013)
In this note, the author prove that maximal Bochner-Riesz commutator B^b_δ,* generated by operator B_δ,* and function bBMO(ω) is a bounded operator from L^p(μ) into L^p( u), where ω(μ u^-1)^1p ,μ, uA_p for 1 < p